Comparative Evaluation of Polarization Colors of Collagen Fibers in Odontogenic Keratocyst and Ameloblastoma Using Picrosirius Red Stain (Histochemical Study) - M.O Bin Hussain, Hawaida; A. Sultan, Azzam (Libyan Journal of Dentistry, 2021)
Aims: studying the quality and quantity of collagen fibers may help to delineate their influence on the aggressiveness and growth potential of the OKC and ameloblastoma. The aims of this study were to evaluate and compare the polarization colors, orientation, and organization of collagen fibers in the connective tissues of the odontogenic keratocyst (OKC), and ameloblastoma (AB) using picrosirius red (PSR) stain under a polarizing microscope with correlation to their biologic behavior. Materials and method: polarization colors, orientation, and organization of collagen fibers in pre-diagnosed cases of OKC and AB, twenty each, and two control cases of dentigerous cyst (DC) were histochemically analyzed using PSR stain and a polarized light microscope. Results: comparing the collagen fibers in the two lesions, there was no significant difference with respect to the polarization colors, orientation, and organization. Conclusion: PSR staining and polarizing microscopy is a powerful tool to appraise the nature and arrangement of collagen fibers in odontogenic lesions. The connective tissue of OKC showed a predominance of green-yellow birefringence, and loosely packed fibers, this can be correlated to the aggressive nature of this lesion.